Propuesta de mejora al proceso de ejecución de proyectos de vinculación con la comunidad en la ESPAM MFL. - Carranza Loor, Martha Verónica (2017)
The Continuous improvement of quality represents a competitive position for institutions, which reflects the capacity and opportunity of the institution and its members. In this context, and in order to contribute to the quality in the Polytechnic School of Agriculture of Manabí, through this research propose improvements to the process of execution of linkage projects. To achieve this objective the inductive, deductive and analytical method was used. In addition to techniques such as: observation and interview, necessary for the obtaining of information. The Value Added Analysis was applied to easily represent the process under study, inputs, outputs, suppliers, customers and inspections of the same, it was also determined the activities that add value to the process of execution of linking projects. Therefore the proposal of improvement to Vice President for Extension and Polytechnic well-being was to: periodically study the level of relevance to community, develop an information system, carry out a project implementation plan and evaluate the results obtained. Therefore, the absence of improvement plans in the institutions of Higher Education causes failures in the administration of their processes, making them few efficient and causing wastage of resources. Therefore, it is necessary to apply corrective actions that help to counteract these problems and perfect the process increase, increasing its efficiency and effectiveness. For Coordination of liaison: work and organize in conjunction with Career Direction the time load to delegates of the Commission of Linkage, monitor and evaluate the activities carried out. For Career Management: to create networks of self-organization and feedback in the departments involved and with the community, to monitor the activities carried out in the planning and to implement approaches of quality and continuous improvement through the management by process, to mitigate the high index of activities that do not add value and waste of resources.